2008
DOI: 10.1021/es702643g
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Of Microbial Urea Hydrolysis In Groundwater To Enhance Calcite Precipitation

Abstract: Addition of molasses and urea was tested as a means of stimulating microbial urea hydrolysis in the Eastern Snake River Plain Aquifer in Idaho. Ureolysis is an integral component of a novel remediation approach for divalent trace metal and radionuclide contaminants in groundwater and associated geomedia, where the contaminants are immobilized by coprecipitation in calcite. Generation of carbonate alkalinity from ureolysis promotes calcite precipitation. In calcite-saturated aquifers, this represents a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(183 citation statements)
references
References 32 publications
4
177
1
1
Order By: Relevance
“…This change in pH can be explained by ureolysis that leads to an increase in pH and a shift in bicarbonate equilibrium. Urea hydrolyzing bacteria can promote calcium carbonate precipitation by hydrolyzing urea and producing ammonium and bicarbonate ions, thereby increasing the pH (Fujita et al, 2008). The generation of NH 4 + increases local pH, and the reaction continues spontaneously to form calcium carbonate in the presence of calcium ions and the availability of nucleation sites (Rodriguez-Navarro et al, 2003).…”
Section: Removal Of Coppermentioning
confidence: 99%
“…This change in pH can be explained by ureolysis that leads to an increase in pH and a shift in bicarbonate equilibrium. Urea hydrolyzing bacteria can promote calcium carbonate precipitation by hydrolyzing urea and producing ammonium and bicarbonate ions, thereby increasing the pH (Fujita et al, 2008). The generation of NH 4 + increases local pH, and the reaction continues spontaneously to form calcium carbonate in the presence of calcium ions and the availability of nucleation sites (Rodriguez-Navarro et al, 2003).…”
Section: Removal Of Coppermentioning
confidence: 99%
“…MICP has also been found to be applicable in various other fields, including the remediation of heavy metals [59], CO 2 sequestration [60], and the repair of concrete [61,62].…”
Section: Attempts With Bio-mineralizationmentioning
confidence: 99%
“…Most earlier studies on environmental urease have been confined to its significance in soil chemistry and agricultural practice. More recent studies have shown that urease-producing microbes show considerable potential for mediating metal bioprecipitation through the formation of insoluble metal carbonates (Fujita et al, 2000(Fujita et al, , 2004(Fujita et al, , 2008Achal, Pan, & Zhang, 2011;Li, Chen & Guo, 2013;Li et al, 2014Li et al, , 2015.…”
Section: Ureasementioning
confidence: 99%
“…MICP has been shown to have potential as a remediation strategy for toxic metals since toxic metals can also be precipitated as insoluble carbonates (Fujita et al, 2000(Fujita et al, , 2004(Fujita et al, , 2008Achal, Pan, & Zhang, 2011;Li, Chen, & Guo, 2013). Furthermore, carbonates can be highly effective in further absorbing toxic metals (Plassard, Winiarski, & Petit-Ramel, 2000;Sipos et al, 2005).…”
Section: Microbially-induced Calcium Carbonate Precipitationmentioning
confidence: 99%